Dissociação devido a evento estressor traumático : precipitadores e tratamento - Guimarães, Eduardo Reuwsaat (2014)
The present work aims to present data on the dissociative phenomena in victims of trauma. Dissociation is defined as changes in the integration of perception and consciousness, provoking states of derealization and depersonalization. It is discussed on literature the role of traumatic stressors, especially if in childhood in the expression of dissociation reactions. Theoretical models propose different levels of importance of the traumatic, and those who argue that the event is a triggering factor or at least a mediator are the ones most empirical support. This dissertation present empirical findings from a clinical assessment in a population of trauma victims. With this, it was aimed to determine the role of different factors as predictors of dissociative symptoms. The empirical study conducted a logistic regression with 47 patients from an outpatient trauma seeking to develop a model considering the main predictors. Results indicated significant predictors, post- traumatic, depressive and anxiety symptoms, as well as trauma and child maltreatment. The role of these findings in different theoretical models on the etiology of dissociative symptoms are discussed. Furthermore, a systematic review aimed to evaluate the effect of different interventions focused on dissociative symptoms in the treatment of Post Traumatic Stress Disorder ( PTSD ). A total of 17 empirical articles were analyzed. All studies point out to a concomitant decrease of dissociative and posttraumatic symptoms, but few studies have directly discuss psychological techniques for solving dissociative symptoms. Both studies point to the association between symptomatologies and suggests that future studies of assessment and treatment of PTSD based on a theoretical model must considers this association.